2020
DOI: 10.3390/catal10020187
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Products Distribution of Enzymatic Hydrolysis Lignin with/without Steam Explosion Treatment by Py-GC/MS

Abstract: This paper investigated the pyrolytic behaviors of enzymatic hydrolysis lignin (EHL) and EHL treated with steam explosion (EHL-SE) by pyrolysis-gas chromatography/mass spectrometer (Py-GC/MS). It was shown that the main component of the pyrolysis products was phenolic compounds, including G-type, H-type, S-type, and C-type phenols. With different treatment methods, the proportion of units in phenolic products had changed significantly. Meanwhile, proximate, elemental, and FTIR analysis of both lignin substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The FTIR spectra of DF from tea residue before and after SE are shown in Figure 4. The absorption peaks near 3,400 cm −1 , 2,920 cm −1 , 1,630 cm −1 , and 1,060 cm −1 represented stretching vibration generated by O-H, C-H, C=O, and C-O-C/O-H of DF, respectively, which conformed to the typical infrared absorption spectrum characteristics of polysaccharides (Ma and Mu, 2015;Dong et al, 2020). After SE treatment, the IDF generated a red shift from 3,400 cm −1 to 3,357 cm −1 (Figure 4A), indicating partial degradation of cellulose and hemicellulose components in the raw material (Zheng et al, 2021).…”
Section: Effect Of Se On the Molecular Structure Of Idf And Sdfsupporting
confidence: 62%
“…The FTIR spectra of DF from tea residue before and after SE are shown in Figure 4. The absorption peaks near 3,400 cm −1 , 2,920 cm −1 , 1,630 cm −1 , and 1,060 cm −1 represented stretching vibration generated by O-H, C-H, C=O, and C-O-C/O-H of DF, respectively, which conformed to the typical infrared absorption spectrum characteristics of polysaccharides (Ma and Mu, 2015;Dong et al, 2020). After SE treatment, the IDF generated a red shift from 3,400 cm −1 to 3,357 cm −1 (Figure 4A), indicating partial degradation of cellulose and hemicellulose components in the raw material (Zheng et al, 2021).…”
Section: Effect Of Se On the Molecular Structure Of Idf And Sdfsupporting
confidence: 62%
“…Under steam explosion at high temperature, high pressure and high humidity, studies have shown that hemicellulose, a heterogeneous multimer consisting of many different monosaccharides, is the most unstable and prone to thermal hydrolysis, producing xylose, arabinose, glucose, galactose, furfural or hydroxymethylfurfural, etc., and hydrolysis of acetyl groups generates organic acids, which also accelerates the decomposition of other substances (Jacquet et al, 2015;Sun et al, 2015). As phenolic polymers, lignin undergoes a series of cleavages, rearrangements and breakdowns that can produce phenolics or phenolic acids and benzene derivatives (Dong et al, 2020). Additionally, cellulose undergoes thermal degradation in which the glycosidic bonds are cleaved to form monosaccharides, and the breaking of the C-C bond in furanose forms small molecules, as similarly occurs in hemicellulose, thereby reducing the absolute cellulose content.…”
Section: Effect Of Different Steam Explosion Conditions On the Textur...mentioning
confidence: 99%
“…Hydrogen ions attack the ether bonds on the hemicellulose molecular chain to cause an electrophilic reaction, promoting the degradation of hemicellulose (Wang et al, 2020). Lignin undergoes a series of cleavages, rearrangements, and breakdowns that can produce phenolics or phenolic acids and benzene derivatives (Dong et al, 2020). The increased moisture of the samples also caused betel nut fiber softening, reducing the mechanical bond strength (Chang et al, 2012).…”
Section: Effect Of Different Steam Explosion Conditions On the Textur...mentioning
confidence: 99%